House rental finder system / Muhammad Shahir Amir Saharudin - Saharudin, Muhammad Shahir Amir (2019)
For the time being, lots of new devices have been produced. Therefore, many developers are competing to produce a great application to ease the public in utilizing the web-based technology. The main intention of this project is to develop and design a web-based application to help users for finding a rental house. Moreover, the web-based application provides the platform for the house owner to advertise their house to the users. This project focuses on two main objectives which are to design and develop a web-based application that has the ability to assist the user to find a house for rental and to evaluate the effectiveness of the system by using User Acceptance Test and Functionality Test. The methodology that has been used to develop the web-based application is the Waterfall Model. This methodology consists of five phases which are planning, requirements analysis, system design, system implementation and testing. In this project, HTML and PHP programming language are involved. In addition, the SQL language has been used as syntax in matters pertaining to the database connection. User Acceptance Test has been performed after all the implementation phase completed. From the User Acceptance Test, it can be concluded that the system is ease to be used and the system gives significant that help users to make their task easier and faster than before. In addition, the functionality test has also been performed to verify that the system and software application can perform and functions perfectly according to the design specifications. From this functionality test, the result shows that all the elements in the system such as, button, text field and images are functionally well and can perform their tasks without any error.